2017
DOI: 10.4314/tjpr.v16i9.6
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in response to improved gedunin by liposomal nano-encapsulation in human non-small-cell lung cancer (NCI-H292) cell line

Abstract: Results: Cell proliferation data and microscopic visualization demonstrated a higher anti-proliferative activity for LG than the encapsulant (liposomes) alone. LG exhibited dose-and time-dependent 10-fold anti-proliferative activity compared to the free drug, while displaying tolerable belligerence towards normal human lung fibroblast (MRC-5) cells. Apoptosis detection assays and gene expression analysis revealed the transcriptional modulation of the apoptosis-related genes (p53, survivin and Bax), increased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…This only had siginifican effects in high doses or in the reproduction/teratogenicity studies. Regarding gedunin toxicity, there are no recent in vivo studies, but low toxicity was described in vitro for adult-derived normal cells, Hs578Bst cells and human mammary epithelial cells (HMEs) [ 68 ], normal pancreatic cells (hTERT-HPNE) [ 69 ], human peripheral blood mononuclear cells [ 70 ], and normal human lung fibroblast (MRC-5) cells [ 71 ].…”
Section: Safety Evaluationmentioning
confidence: 99%
“…This only had siginifican effects in high doses or in the reproduction/teratogenicity studies. Regarding gedunin toxicity, there are no recent in vivo studies, but low toxicity was described in vitro for adult-derived normal cells, Hs578Bst cells and human mammary epithelial cells (HMEs) [ 68 ], normal pancreatic cells (hTERT-HPNE) [ 69 ], human peripheral blood mononuclear cells [ 70 ], and normal human lung fibroblast (MRC-5) cells [ 71 ].…”
Section: Safety Evaluationmentioning
confidence: 99%
“…Cazal et al [31] concluded that gedunin arrested the cell cycle progression in the S phase, leading to a decrease in the percentage of cells in the G1 phase, thus inducing apoptosis. Recently, the anti-proliferative activity of free and nanoencapsulated gedunin against human non-small-cell lung cancer (NCI-H292) cells was investigated by Nwokwu et al [41], demonstrating that liposomal gedunin has greater anti-proliferative effects in NCI-H292 cells than free gedunin, with IC 50 values ranging from 3.4 to 1.8 µg/mL (24 to 72 h) and 26.4 to 21.6 µg/mL (24 to 72 h), respectively. These authors also studied the apoptotic effect of gedunin-loaded liposomal nanoparticles in NCI-H292 cell line and concluded that it enhances anti-proliferative effects through p53-initiated, Bax-associated, caspase-dependent activation of apoptosis.…”
Section: Lung Cancermentioning
confidence: 99%
“…The IC 50 value obtained was >100 µg/mL for all incubation periods tested (24,48, and 72 h), which means gedunin is not cytotoxic to these cells. Nwokwu et al [41] tested gedunin and gedunin-loaded liposomal nano-particles on normal human lung fibroblast (MRC-5) cells at different experimental timelines 24, 48, and 72 h. The compound itself presented IC 50 values of > 50 µg/mL at all times tested and gedunin liposomes presented IC 50 values of 5.32, 2.94, and 4.90 µg/mL for 24, 48, and 72 h, respectively. Nevertheless, gedunin liposomes were less toxic than the control drug used, paclitaxel (p < 0.05).…”
Section: Toxicitymentioning
confidence: 99%
“…However, there is a great potential with the limited number of scientists who are actively associated with research in nano-drug carriers, antibacterial agents, and bone prostheses. These include development of bone prostheses (Rajapakse et al, 2016), drug encapsulation, for example, Vitamin C (Samantha Dissanayake et al, 2015), targeted cancer treatment (Katuwavila et al, 2016a;Weerasuriya et al, 2017;Nwokwu et al, 2017;Manatunga et al, 2017;Manatunga et al, 2018a), and developing antimicrobial agents (Peiris et al, 2017;Rathnayake et al, 2018). Rajapakse et al have actively engaged in nano hydroxyapatite-based biomaterials ( Fig.…”
Section: State Of Nanomedicine Research In Sri Lankamentioning
confidence: 99%
“…Most of these drug delivery systems are based on chitosan alginate nanoparticles (Katuwavila et al, 2016a;Katuwavila et al, 2016b) or liposomes (Samantha Dissanayake et al, 2015;Pamunuwa et al, 2016;Pamunuwa et al, 2015;Menikarachchi et al, 2016;Nwokwu et al, 2017). They have been tested on various cancer cell lines such as breast (Katuwavila et al, 2016a) and lung (Nwokwu et al, 2017) cancer. Even though there is a good potential of these drugs to act against cancer cells, none has reached the clinical stage.…”
Section: State Of Nanomedicine Research In Sri Lankamentioning
confidence: 99%